Amphetamine Modestly Improves Conners' Continuous Performance Test Performance in Healthy Adults. (16th October 2017) - MacQueen, David A.; Minassian, Arpi; Henry, Brook L.; Geyer, Mark A.; Young, Jared W.; Perry, William
Abstract: Objectives: Amphetamine improves vigilance as assessed by continuous performance tests (CPT) in children and adults with attention deficit hyperactivity disorder (ADHD). Less is known, however, regarding amphetamine effects on vigilance in healthy adults. Thus, it remains unclear whether amphetamine produces general enhancement of vigilance or if these effects are constrained to the remediation of deficits in patients with ADHD.Methods: We tested 69 healthy adults (35 female) on a standardized CPT (Conner's CPT-2) after receiving 10- or 20-mg d-amphetamine or placebo. To evaluate potential effects on learning, impulsivity, and perseveration, participants were additionally tested on the Iowa Gambling Task (IGT) and Wisconsin Card Sorting Task (WCST).Results: Participants receiving placebo exhibited the classic vigilance decrement, demonstrated by a significant reduction in attention (D') across the task. This vigilance decrement was not observed, however, after either dose of amphetamine. Consistent with enhanced vigilance, the 20-mg dose also reduced reaction time variability across the task and the ADHD confidence index. The effects of amphetamine appeared to be selective to vigilance since no effects were observed on the IGT, WCST, or response inhibition/perseveration measures from the CPT.Conclusions: The present data support the premise that amphetamine improves vigilance irrespective of disease state. Given that amphetamine is a norepinephrine/dopamine transporter inhibitor and releaser, these effects are informative regarding the neurobiological substrates of attentional control. ( JINS, 2018, 24, 283–293)